2022
DOI: 10.1080/20018525.2022.2149919
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 in athletes (COVA) study: a national study on cardio-pulmonary involvement of SARS-CoV-2 infection among elite athletes

Abstract: Background COVID-19 can cause cardiopulmonary involvement. Physical activity and cardiac complications can worsen prognosis, while pulmonary complications can reduce performance. Aims To determine the prevalence and clinical implications of SARS-CoV-2 cardiopulmonary involvement in elite athletes. Methods An observational study between 1 July 2020 and 30 June 2021 with the assessment of coronary biomarkers, electrocardiogram, echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Taken together, our findings are in line with previous reports, which suggest that cardiac sequelae after infection with SARS-CoV-2 among athletes seems to be less frequent than assumed in the initial phase of the pandemic. Similar to others [ 1 , 23 , 33 ], no severe cardiac events have been reported up to now in our study population. However, a remaining risk of an acute myocardial involvement in athletes with SARS-CoV-2 infection must be kept in mind and long-term effects on the heart cannot be excluded.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together, our findings are in line with previous reports, which suggest that cardiac sequelae after infection with SARS-CoV-2 among athletes seems to be less frequent than assumed in the initial phase of the pandemic. Similar to others [ 1 , 23 , 33 ], no severe cardiac events have been reported up to now in our study population. However, a remaining risk of an acute myocardial involvement in athletes with SARS-CoV-2 infection must be kept in mind and long-term effects on the heart cannot be excluded.…”
Section: Discussionsupporting
confidence: 92%
“…No evidence of spirometric impairments were reported in competitive athletes [ 25 ] but also in a larger number of young healthy adults [ 34 ]. In contrast, Rasmusen et al found an obstructive lung function or radiological signs of COVID-19 in 15 of 122 elite athletes after SARS-CoV-2 infection [ 33 ]. It cannot be ruled out that a more comprehensive pulmonary diagnostic procedure including the assessment of diffusion capacity and respiratory muscle strength may reveal abnormal results relevant for exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort of professional football players, aerobic capacity was decreased 60 days after infection (Parpa & Michaelides, 2022). Likewise, a cohort of 10 different sports disciplines showed that the exercise capacity of athletes decreased during the acute infection period (Rasmusen et al., 2022). The present study, reporting data from an elite athlete cohort, suggests that physiological deteriorations may prolong recovery time, in accordance with previously reported findings (Hull et al., 2022), however, the respiratory capacity of athletes with primary infection typically recovers significantly within 6 months, suggesting that this could potentially allow them for an earlier resumption of routine training compared to those with reinfections.…”
Section: Discussionmentioning
confidence: 99%